Assessment of medication adherence in Helicobacter pylori positive patients on standard triple therapy: a prospective study - Francis, Aleena; Nair, Arathi S.; Gomez, Limi Joseph; Rahim, Bushra Abdul; V., Soumya R.; R., Prasobh G. (International Journal of Basic & Clinical Pharmacology, 2020)
Background: In the current study patient compliance to the standard triple therapy were assessed. The objective behind this research was to assess the patient medication adherence to the standard triple therapy in Helicobacter pylori infection. Methods: A prospective study was carried out for a period of 1 year and samples were taken from the gastroenterology department. Patient who was RUT (rapid urease test) positive by endoscopy were considered as H. pylori infected and they were prescribed with standard triple therapy. This regimen involves amoxicillin 1000 mg and clarithromycin 500 mg and proton pump inhibitor (PPI) twice a day for 14 days. Adherence to this triple therapy was assessed during the study. Medication adherence assessed using Morisky, Green and Levine (MGL) adherence scale. MGL adherence questionnaire was given to patients during first week and second week of therapy. The patients will be counselled regarding the drug administration, drug related problems and the infection. They were also provided with written instructions in leaflets. 88 patients were analyzed. Results: In this study, 84 patients had a good adherence 95.5%; but other 4.5% didn’t fully comply with the physician’s order. After the first week of standard triple therapy, adherence was increased to a mean score from 2.193±0.1301 to 3.5227±0.0704 in the second week. The medication adherence score significantly increased along with patient counselling. Conclusions: Medication adherence was improved in the 14 days course along with patient education helped to comply with the standard triple therapy.